The Factors Contributing to Domestic Violence from the Perspective of Iranian Couples: A Qualitative Study - roghieh bayrami; ali vafaee najar (Kerman University of Medical Sciences, 2020)
Introduction: Domestic violence is the most common form of violence against women. Negative health outcomes caused by domestic violence have been recognized as a public health problem with extensive effects on society. The main objective of this study was to explore Iranian couples' experiences of domestic violence. Methods: This study was carried out through a qualitative approach and a conventional content analysis method in 2015 in Mashhad, Iran. Fifteen couples (15 women and 15 men) were selected from five health centers in Mashhad using purposive sampling. Data were collected through individual in-depth semi-structured interviews with the participants about their perceptions and experiences of factors underlying domestic violence. The interviews were transcribed verbatim and analyzed using Graneheim and Lundman's content analysis approach with MAXQDA software. Results: The results of this study revealed three main themes including social factors affecting violence (the family's economic position, culture and values, and social support), interpersonal relations (the type of marriage and life skills), and personal factors (intrinsic factors and acquired factors). Conclusion: Given that social, interpersonal, and personal factors such as economic problems, social culture, low social support, low education levels, addiction, and the absence of life skills can lead to the outbreak of domestic violence among couples, there is a need to train couples to adopt effective strategies to reduce domestic violence in the family and seek help from support centers.